Pengaruh Asset Growth, Leverage, And Corporate Social Responsibility (CSR) On Firm Value - Sulastri, Sulastri (CV. ITTC INDONESIA, 2024)
This study aims to examine and analyze the effect of asset growth, leverage, corporate social responsibility on firm value in plastic and packaging sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The population used in this study were all plastic and packaging sub-sectors listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period, totaling 13 companies, while the sample in this study found 10 companies taken using purposive sampling technique. The type of data in this study is quantitative data. The data analysis techniques used in this research are descriptive statistical analysis, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that asset growth has significant effect on firm value, leverage has no significant effect on firm value, corporate social responsibility has significant effect on firm value, and asset growth, leverage, corporate social responsibility simultaneously have significant effect on firm value. The value of the coefficient of determination is 0.379 which indicates that asset growth, leverage and corporate social responsibility have a proportion of 37.9% influence on firm value. While the remaining 62.1% can be explained by other factors outside the variables in this study.